2015
DOI: 10.1093/cercor/bhv296
|View full text |Cite
|
Sign up to set email alerts
|

Local GABA Concentration Predicts Perceptual Improvements After Repetitive Sensory Stimulation in Humans

Abstract: Learning mechanisms are based on synaptic plasticity processes. Numerous studies on synaptic plasticity suggest that the regulation of the inhibitory neurotransmitter γ-aminobutyric acid (GABA) plays a central role maintaining the delicate balance of inhibition and excitation. However, in humans, a link between learning outcome and GABA levels has not been shown so far. Using magnetic resonance spectroscopy of GABA prior to and after repetitive tactile stimulation, we show here that baseline GABA+ levels predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 47 publications
4
39
0
1
Order By: Relevance
“…Previous MRS studies reported correlations between behavioral or neurophysiological measures and GABA estimates within targeted brain regions (Bachtiar et al, 2015; Balz et al, 2016; Boy et al, 2010; Heba et al, 2016; Jocham et al, 2012; Stagg et al, 2011a; 2011b; Sumner et al, 2010; van Loon et al, 2013). For example, resting GABA content in primary motor cortex was positively correlated with individual differences in motor sequence reaction time (Stagg et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…Previous MRS studies reported correlations between behavioral or neurophysiological measures and GABA estimates within targeted brain regions (Bachtiar et al, 2015; Balz et al, 2016; Boy et al, 2010; Heba et al, 2016; Jocham et al, 2012; Stagg et al, 2011a; 2011b; Sumner et al, 2010; van Loon et al, 2013). For example, resting GABA content in primary motor cortex was positively correlated with individual differences in motor sequence reaction time (Stagg et al, 2011a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, we have shown that GABA in the occipital cortex correlates with performance on a visual orientation discrimination task (Edden et al, 2009) and that GABA measured in the sensorimotor cortex correlates with performance on a behavioral tactile frequency discrimination task (Puts et al, 2011). Other studies have shown correlations between in vivo GABA levels and individual differences in motor suppression (Boy et al, 2010), motor learning (Bachtiar and Stagg, 2014; Floyer-Lea et al, 2006), and the effect of peripheral modulation (Heba et al, 2016). Many of the studies also show that correlations between GABA and behavior are functionally and regionally specific.…”
Section: Introductionmentioning
confidence: 99%
“…γ-Aminobutyric-acid (GABA) is the main inhibitory neurotransmitter in the brain, and is important in shaping the neuronal responses to sensory stimulation (Bruno and Simons, 2002; Dykes et al, 1984), in plasticity, learning and memory (Heba et al, 2016; McCormick, 1989; Michels et al, 2012; Stagg et al, 2011). GABA has been implicated in a number of psychiatric, neurological and developmental disorders (Chang et al, 2003; Puts and Edden, 2012; Sanacora et al, 2006; Simister et al, 2003) and our previous work has shown a link between altered GABA and abnormal sensory function in autism spectrum disorder (Puts et al, 2016) and Tourette syndrome (Mahone et al, 2018; Puts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These associations are reviewed by Puts and Edden (2012) and by Schür et al (2016). Measures of GABA levels appear to be functionally and regionally specific, and studies have shown associations between sensorimotor GABA levels and tactile sensitivity (Heba et al, 2016;Puts et al, 2011Puts et al, , 2015, between occipital GABA levels and visual orientation discrimination (Edden et al, 2009;Yoon et al, 2010), between motor cortex GABA and motor control and learning (Bachtiar and Stagg, 2014;Stagg et al, 2009Stagg et al, , 2011a, between anterior cingulate cortex and response inhibition (Silveri et al, 2013), and between frontal GABA concentrations and working memory (Michels et al, 2012). For a review, see Duncan et al (2014).…”
mentioning
confidence: 99%